The cultural landscape & heritage paradox : protection and development of the Dutch archaeological-historical landscape and its European dimension - Bloemers, J. H. F.; Bodemarchief in Behoud en Ontwikkeling ([Amsterdam] : Amsterdam University Press, 2010)
The basic problem is to what extent we can know past and mainly invisible landscapes, and how we can use this still hidden knowledge for actual sustainable management of landscape's cultural and historical values. It has also been acknowledged that heritage management is increasingly about 'the management of future change rather than simply protection'. This presents us with a paradox: to preserve our historic environment, we have to collaborate with those who wish to transform it and, in order to apply our expert knowledge, we have to make it suitable for policy and society. The answer presented by the Protection and Development of the Dutch Archaeological-Historical Landscape programme (pdl/bbo) is an integrative landscape approach which applies inter- and transdisciplinarity, establishing links between archaeological-historical heritage and planning, and between research and policy.
Includes bibliographical references and indexes.
boek
Keywords: Historic preservation -- Europe; Cultural property -- Protection; Landscape archaeology -- Europe; Historic preservation -- Netherlands; Landscape archaeology -- Netherlands